Comparison Study of Subtropical Mode Waters in the World Ocean - Tsubouchi, Takamasa; Suga, Toshio; Hanawa, Kimio (Frontiers in Marine Science, 2016)
Subtropical Mode Water (STMW) is a distinctive upper ocean structure in the western part of subtropical gyres in the world ocean. This paper proposes a common criterion of STMW to quantify and compare spatial structures of STMWs in different basins. STMW can be defined as a thermostad (a layer weakly stratified in temperature) by applying a criterion of averaged core layer temperature (CLT)±1ºC with its layer thickness greater than 100 m. Two features are highlighted when comparing the STMWs in different basins. Firstly, the North Atlantic hosts the thickest STMW in the world ocean. Secondly, the South Atlantic STMW has an unique vertical structure of density compensating temperature and salinity stratification. By comparing the thickness of STMW against the strength of winter cooling and the volume transport of associated western boundary current (WBC) in different basins, it is shown that thicker STMW tends to be accompanied with stronger WBC. From a view point of vorticity dynamics, we suggest that the North Atlantic may have the most efficient condition to host the thickest STMW and the strongest recirculation gyre in the world ocean.